DISCOURSE MARKERS IN POLITICAL SPEECHES OF AMERICAN AND INDONESIAN PRESIDENTS - Lalu Thohir (Cordova Journal : languages and culture studies, 2016)
Abstract: Discourse Markers can be defined as expressions which relate discourse segments. Discourse markers analyzed and compared in this study are lexical cohesions in political speeches of the American and Indonesian presidents. In this study, the writer used descriptive qualitative method. The method includes collecting, arranging, classifying, analyzing, and interpreting the data. The data for the English political speeches were taken from Washingtonpast.com and Federal News Service, and those for the Indonesian political speeches were taken from suara Surabaya.net and TEMPO.CO.JAKARTA. The result of this study shows that the lexical cahesions as discourse markers in both languages are generally similar except the position where they accur. In English, lexical cohesions might accur in three positions in a sentence: Initial, medial and final positions with special meaning for each position, while lexical cohesions in Indonesian language might not do as they accur only in the initial and medial positions, and not in the final position. In addition, it also shows that lexical cohesions in English political speeches are used more frequently than those in Indonesian political speeches.